Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 6 - Section 6.2 - Adding and Subtracting Rational Expressions - 6.2 Exercises: 54

Answer

$\frac{2x+3}{x(x-3)}$

Work Step by Step

$\frac{3}{x-3}-\frac{1}{x}=\frac{3\times x}{(x-3)\times x}-\frac{1\times(x-3)}{x\times(x-3)}=\frac{3x}{x(x-3)}-\frac{x-3}{x(x-3)}=\frac{3x-(x-3)}{x(x-3)}=\frac{3x-x+3}{x(x-3)}=\frac{2x+3}{x(x-3)}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.